Testes preliminares de motilidade intestinal e toxicidade oral aguda com extrato de cascas pulverizadas de Endopleura uchi (Huber) Cuatrec: (Humiriaceae) em camundongos - Politi, Flávio Augusto Sanches [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Pietro, Rosemeire Cristina Linhari Rodrigues [UNESP]; Moreira, Raquel Regina Duarte [UNESP] (My University, 2010)
The aim of this work was to analyze the acute oral toxicity and the effects on intestinal motility of the extract obtained through decoction 20% (m/v) of Endopleura uchi, popularly known as "uxi-amarelo", a native plant from the Brazilian Amazon. The plant is used indiscriminately against several diseases: arthritis, cholesterol, diabetes, ulcers, myomas, and intestinal illnesses in general, among others. The present results show that there were no significant alterations in intestinal motility and that the extract does not present signs of toxicity, showing its safety for consumption purposes.

El objetivo de este estudio fue evaluar los efectos sobre la motilidad intestinal y la toxicidad oral del extracto obtenido por decocción al 20% (m/v) de Endopleura uchi, cuyo nombre común brasileño es "uxi-amarelo". Se trata de una planta nativa de la Región Amazónica brasileña, utilizada de forma indiscriminada en la lucha contra diversas enfermedades: artritis, colesterol, diabetes, úlceras, fibromas, trastornos intestinales en general, entre otras. Los resultados mostraron que no hubo alteraciones significativas en la motilidad intestinal y que el extracto no muestra indicios de toxicidad, proporcionando seguridad para su consumo.

O objetivo deste trabalho foi avaliar os efeitos sobre a motilidade intestinal e a toxicidade oral aguda de extrato obtido por decocção 20% (m/v) de Endopleura uchi, popularmente conhecido como uxi-amarelo, planta nativa da Região Amazônica brasileira, utilizada indiscriminadamente para o combate de diversas doenças: artrite, colesterol, diabetes, úlceras, miomas, afecções intestinais de uma forma geral, entre outras. Os resultados mostraram que não houve alteração significativa na motilidade intestinal e que o extrato não apresenta traços de toxicidade, conferindo segurança para seu consumo.
Preliminary tests on acute oral toxicity and intestinal motility with extract of pulverized bark of Endopleura uchi (Huber) Cuatrec: (Humiriaceae) in mice
Pruebas preliminares de motilidad intestinal y de toxicidad oral aguda con extracto de corteza en polvo de Endopleura uchi (Huber) Cuatrec: (Humiriaceae) en ratones
Keywords: Endopleura uchi; Gastrointestinal motility; Acute toxicity; Phytotherapy; Plant extracts; Endopleura uchi; Motilidad gastrointestinal; Toxicidad aguda; Fitoterapia; Extractos vegetales; Endopleura uchi; Motilidade gastrointestinal; Toxicidade aguda; Fitoterapia; Extratos vegetais